How do people with multiple long-term health conditions experience the self-management approach to health care? : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, Palmerston North, New Zealand - Francis, Helen Catherine (Massey University, 2017)
The health system in New Zealand has devised approaches intended to meet the needs of people with long-term conditions (LTCs) based on the international theories of the Chronic Care Model (CCM) and a self-management framework (Bodenheimer, Wagner, & Grumbach, 2002b; Lorig, 1993; Wagner, 1998). LTCs and multimorbidity are socially patterned so often people with several LTCs are also contending with chaotic lives as well as the implications of their Illnesses. The self-management framework is based on the assumption that everyone has the agency or freewill to make the daily decisions that would benefit their health and ignores the powerful effect of social context. Because the behaviours recommended to optimise health are so entwined with a person’s social context, LTCs are particularly sensitive to the social determinants of health. This multiple case study follows the complex lives of sixteen people with several significant long-term health conditions using the theories of both Cockerham (2005, 2010, 2013b) and Link and Phelan (1995, 2010) to explore their experiences. Ongoing contact with the patient-participants comprised two interviews, four-weekly contacts and interviews with their primary health care clinicians. The patient-participants’ stories reveal complex, entangled lives marked by loss, poverty and daily challenges. They are significantly constrained by the overwhelming social contexts of their lives and reduced to survival mode by their cumulative losses across the four domains of the Whare Tapa Wha model. Personal agency is neither a choice nor readily achieved. They are left too exhausted to work their way through a health system that does not recognise their needs, empower them or compensate for their lack of energy. The weary patient-participants in this study bear little resemblance to the idealised expert patient of the self-management framework. Clinicians are left manoeuvring to compassionately and pragmatically support the patient-participants as best they can within an unhelpful system. The findings however do surface examples of care that are valued by both patient-and clinician-participants that sit outside the self-management approach. These valued aspects are explored alongside the harm reduction, recovery and palliative models of care. These all offer contributions towards an approach that would optimise the quality of life for people with significant, multiple LTCs. An exploration of this re-awakened approach to care is described. Care that is constricted self-management approach could wrap around the patient and support them to use their residual agency in a direction of their choosing. Clinicians would be released from their current programmed response be able to more fully utilise their clinical expertise. Clinicians and patients would have the freedom to be more pragmatic around quality of life and the issues that matter to the individual with LTCs.
Keywords: Self-care, Health; Chronically ill; Comorbidity; Maori; Health and hygiene; New Zealand; Hauora